Using national health weeks to deliver deworming to children: lessons from Mexico. Issue 4 (13th March 2008) - Flisser, A; Valdespino, J L; García-García, L; Guzman, C; Aguirre, M T; Manon, M L; González-González, G; Gyorkos, T W
Abstract : Mexico established national health weeks (NHWs) in the early 1980s to promote childhood vaccinations. Because of the cumulative worldwide peer-reviewed scientific evidence, the recommendations of the World Health Organization and other international organisations, the political will of the Mexican government and the infrastructure provided by the NHWs, deworming was added to the NHWs in 1993. In addition to the Ministry of Health, several other government organisations participated in administering the deworming component. Tens of millions of school-age and preschool children between the ages of 2 years and 14 years now receive deworming (a single 400 mg dose of albendazole) approximately every 8 months. Between 1993 and 1998 evaluations were carried out in over 90 000 children to determine the effect of NHWs on the prevalence of geohelminth infections. In 1993, the overall prevalence of Ascaris was 20% and that of Trichuris was 15%. Prevalences decreased significantly over time (p <0.001). Treatment efficacy for Ascaris ranged from 91.6% to 85.3%, and for Trichuris, from 97.9% to 42.6%. In 1998, after conducting 12 NHWs with deworming, the respective prevalences were Ascaris 8% and Trichuris 11%. The experience of Mexico in integrating albendazole into its NHWs shows how deworming can be delivered to large numbers of at-risk children using an existing infrastructure. The NHW approach may be generalisable in other countries with successful national vaccination campaigns. The challenge remaining is to sustain the deworming programme until other longer-term behavioural, environmental and socioeconomic changes can be implemented.